Analysis of The Logistics Performance Index Based on Regional Economic Integration: Evidence from ECOWAS - YERDELEN KAYGIN, Ceyda; KAHRAMANİ KOÇ, Azize (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The regional economic integration mainly aims to eliminate national borders for generating a worldwide market. The construction of logistical infrastructure functions as the crucial foundation since it allows member countries to meet their economic development goals. The Logistics Performance Index (LPI) success rankings of the Economic Community of West African States (ECOWAS) were analyzed employing the LOPCOW and CoCoSo techniques. As a result, different criteria emerged as prominent factors affecting the high levels of LPI success rankings of countries throughout the years. The “infrastructure” criterion was defined as a key factor over the years 2023 and 2012 in Benin, whereas the “timeliness” criterion has been crucial in 2018, and the “customs” criterion was effective in 2010. The “tracking and tracing” criterion functioned as an important factor throughout 2016 in Burkina Faso. The “international shipments” criterion was successful during 2014 in Nigeria. The “tracking and tracing” criterion in 2023 and the timeliness criterion in 2012 proved to be the main reasons for low LPI success rankings in Burkina Faso. The “customs” criterion proved important for Liberia in 2018 but the “infrastructure” criterion stood out in 2016. The “logistics competence and quality” criterion served as a key factor in Guinea-Bissau during 2014 but the “timeliness” criterion delivered results in 2010.